HASIL EVALUASI PENGGUNAAN GENTAMISIN UNTUK TERAPI PNEUMONIA PADA PASIEN GERIATRI RAWAT INAP DI RUMAH SAKIT UMUM PUSAT DR. SARDJITO YOGYAKARTA - , Endah Nurrohwinta D; , Prof. Dr. Djoko Wahyono, SU., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Geriatric patients experienced a decrease in the physiological condition of the body. Geriatric susceptible to infections and chronic diseases. Type of infection experienced by geriatric one of which is pneumonia. One of pneumonia therapy using an aminoglycoside class of antibiotics gentamicin examples that have a narrow therapeutic index. Changes in physiological conditions in geriatrics will affect the pharmacokinetics and pharmacodynamics of drugs, so that the necessary monitoring and dose adjustments to prevent toxic effects. The purpose of this study was to obtain profiles of gentamicin dose for pneumonia therapy in geriatric patients, knowing predictions peak levels ( ) and trough levels ( ) in the blood gentamicin for pneumonia therapy in geriatric patients, determine clinical outcomes in the treatment of geriatric patients gentamicin combination with other antibiotics to treat pneumonia, knowing the side effects of gentamicin in the treatment of pneumonia in the form of rise in serum creatinine. This study was a retrospective case series descriptive design. Subjects were geriatric patients who developed pneumonia were treated with gentamicin in 2012-2013. The number of patients who meet the inclusion and exclusion criteria for this study were as many as 14 patients. Research shows that profiles gentamicin dose for pneumonia therapy in geriatric patients is ranging from 1-5 mg / kg / day. Predicted peak levels ( ) and trough levels ( ) gentamicin in the blood was 15.3 Â± consecutive 4.46 mg / mL and 0.4 Â± 0.6 mg / mL. The percentage of geriatric patients improved clinical outcomes in combination therapy with other antibiotics gentamicin was 57.14% for the 8 patients of the total 14 patients. The percentage of gentamicin side effects such as an increase in serum creatinine was 14.28% for the 2 patients of the total 14 patients.